Case Report: Propranolol Therapy for Infantile Tremor Syndrome in a Child With Vitamin B12 Deficiency - Cyr, Amélie; Frehlick, Ryan; Stammers, David; Crone, Megan (Frontiers in Pediatrics, 2021)
Vitamin B12 deficiency in childhood presents with a wide variety of symptoms including anemia, failure to thrive and developmental delays. It is a diagnostic consideration in children who are exclusively breastfed or have minimal solid intake, especially if their mother is vegetarian or has underlying vitamin B12 deficiency. Infantile tremor syndrome (ITS) has been associated with vitamin B12 deficiency. ITS presents with neurological symptoms such as developmental delays and tremors. The tremors seen in ITS can be profound and interfere with daily functioning. Different therapies have been tried for those tremors without much evidence or information regarding their efficacy and dosing regimens. We present the case of a 13-month-old girl with vitamin B12 deficiency who developed ITS with significant tremors after initiation of vitamin B12 therapy. She was treated with propranolol which resulted in significant improvement in her tremors. This case highlights the efficacy and safety of propranolol for the treatment of ITS in the context of vitamin B12 deficiency.